Enhancing osteogenic potential of hDPSCs by resveratrol through reducing oxidative stress via the Sirt1/Nrf2 pathway - Jingying Zhang; Rui Li; Kenny Man; Xuebin B. Yang (Taylor & Francis Group, 2022)
Context The osteogenic potential of the human dental pulp stromal cells (hDPSCs) was reduced in the state of oxidative stress. Resveratrol (RSV) possesses numerous biological properties, including osteogenic potential, growth-promoting and antioxidant activities. Objective This study investigates the osteogenic potential of RSV by activating the Sirt1/Nrf2 pathway on oxidatively stressed hDPSCs and old mice. Materials and methods The hDPSCs were subjected to reactive oxygen species (ROS) fluorescence staining, cell proliferation assay, ROS activity assay, superoxide dismutase (SOD) enzyme activity, the glutathione (GSH) concentration assay, alkaline phosphatase staining, real-time polymerase chain reaction (RT-PCR) and Sirt1 immunofluorescence labelling to assess the antioxidant stress and osteogenic ability of RSV. Forty female Kunming mice were divided into Old, Old-RSV, Young and Young-RSV groups to assess the repair of calvarial defects of 0.2 mL RSV of 20 mg/kg/d for seven days by injecting intraperitoneally at 4 weeks after surgery using micro-computed tomography, nonlinear optical microscope and immunohistochemical analysis. Results RSV abates oxidative stress by alleviating the proliferation, mitigating the ROS activity, increasing the SOD enzyme activity and ameliorating the GSH concentration (RSV IC50 in hDPSCs is 67.65 ± 9.86). The antioxidative stress and osteogenic capabilities of RSV were confirmed by the up-regulated gene expression of SOD1, xCT, RUNX2 and OCN, as well as Sirt1/Nrf2. The collagen, bone matrix formation and Sirt1 expression, are significantly increased after RSV treatment in mice. Discussion and conclusions For elderly or patients with oxidative stress physiological states such as hypertension, heart disease, diabetes, etc., RSV may potentially improve bone augmentation surgery in regenerative medicine.